1995
DOI: 10.1111/j.1471-0528.1995.tb10844.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of recurrent genital herpes infection in pregnancy: a postal survey of obstetric practice

Abstract: Objective To determine clinical practice amongst bstetricians in the UK in the antepartum and intrapartum management of pregnant women with recurrent genital herpes infection. Methods All Members and Fellows of the Royal College of Obstetricians and Gynaecologists resident in the UK were sent a questionnaire requesting information concerning their management of pregnant women with recurrent genital herpes infection. Results There was a 76% response rate to the questionnaire. Of the 1201 obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Similar discrepancies were noted in a study from the United Kingdom. 6 Trainees were more familiar with recent developments. For instance, in the case of ruptured membranes of more than 4 hours with a HSV recurrence where there is little evidence that performing a caesarean section would reduce risk to the baby, 8 9 trainees were significantly less likely to perform a caesarean section when compared with fellows.…”
Section: Discussionmentioning
confidence: 99%
“…Similar discrepancies were noted in a study from the United Kingdom. 6 Trainees were more familiar with recent developments. For instance, in the case of ruptured membranes of more than 4 hours with a HSV recurrence where there is little evidence that performing a caesarean section would reduce risk to the baby, 8 9 trainees were significantly less likely to perform a caesarean section when compared with fellows.…”
Section: Discussionmentioning
confidence: 99%
“…Ключевыми элементами данной экосистемы являются вагинальный эпите-лий и вагинальная флора [4,14,15,16].…”
Section: обзор литературных данныхunclassified
“…If there is evidence of an active recurrence then delivery by caesarean section is recommended to avoid the risk of mother to child transmission. 5 If there is no evidence of an active recurrence then a vaginal delivery is anticipated. The risk of mother to child transmission is unknown but estimates suggest that it can be no higher than 8%6 although many authorities believe it is significantly lower than this and some have suggested that it is negligible.7 As a consequence of the current management policy many women with recurrent genital herpes infection present at the time of labour undergo caesarean section when the risk to the neonate appears to be small.…”
Section: Introductionmentioning
confidence: 99%